THE MECHANICAL BEHAVIOR OF DENTAL BRIDGES ACCORDING WITH THEIR LINEAR OR NON-LINEAR SUPPORT-A MATHEMATICAL MODEL - Nicoleta Ioanid; Maria Alexandra Mârțu; Irina Georgeta Șufaru; Roxana Vasluianu; Raluca Baciu (Romanian Society of Oral Rehabilitation, 2021)
The prosthetic restorative dentistry is based on more or less current principles, laws and concepts. The design, construction and well-fitting of the prostheses must ensure their sustainability but also the one of the supporting tissues. AIM. Mechanical forces effect (forces different in application, orientation and intensity) on dental bridges multiple tooth-supported by using mathematical models. MATERIAL AND METHODS. We imagined theoretical models of analysis, starting from the case of linear support on two teeth, respectively three teeth. Then, we studied the case of nonlinear support. The prosthesis was assimilated with a bar rigidly fixed at both ends, with a simple geometry, supported on pillars with the same resistance, anchored in resilient supports, with the same constant of elasticity. Then, the established reference system was stressed with a force whose vector and scalar quantities are considered known. RESULTS. CONCLUSIONS. Rigid systems with non-collinear support exert forces of the same magnitude on support structures as those with collinear support.